STUDI TENTANG UKIRAN PADA MIMBAR DAN MAQSURAH MASJID BINGKUDU V SUKU CANDUANG - PUTRA MURDANI, Drs. Syafril R. M.Pd, Drs. Syafei,M.Ag (Serupa The Journal of Art Education, 2014)
The purposes of this study were to (1) describe the form of wood carving ornament that used at Mimbar and Maqsurah of Bingkudu Mosque, (2) describe the meaning and the grounded meaning of wood carving ornament that used at Mimbar and Maqsurah of Bingkudu Mosque. The Bingkudu Mosque is the ancient Mosque was builded about the end of 19 centuries in V Suku Canduang Minangkabau. That Mimbar and Maqsurah based on observasion have some unique carving form liked Netherland flag form, chaligraphy, and traditional carving with red and gold color. They were assumed have the meaning related to tradistional culture, religism, history, and colonial period and more how the implicated of “adat basandi syarak, syarak basandi kitabullah” especially in carving as society’s works of art. The primary source of data were oral untterances uttered by native speaker informants and some literatures or books. Data were collected by using observation methods, field note as advanced techniques, and photos. The process called as snow balling to get the holistic data. The finding of the study showed that the form, meaning, and grounded meaning of the carving have some relationship meaning with the function of Surau, Islamic religion, Minangkabau culture, the fungtioned of three commader symbol in Minangkabau and colonial perioded in Minangkabau, and ensure that between islamic religion and traditional culture of Minangkabau were had a single vission.Key words: Mosque, Carving, Mimbar and Maqsurah, culture, Minangkabau, form, meaning and grounded meaning